The evolution of spanish commitment to peacekeeping operations. an image of Spain abroad 1989-2014 (Comillas Journal of International Relations, 2014)
As a member of the International Community, Spain has transformed in ways that could barely have been envisaged back in the late 70s and the beginning of the Transition. Notwithstanding the objective data, the image of Spain and how Spain is perceived in the world depends on many factors and evolves over time.  Undoubtedly, Peacekeeping Operations constitute an excellent stage whereby Spain can project and promote its image, while at the same time providing an interesting index analysis to determine the vision its own people and other states have of Spain. Images are key to the reliability and reputation of a state in international relations, and crucial to strategies affecting the national branding of a country.  With 25 years of involvement, and more than 60 peacekeeping operations, these actions are fundamental to the strategic image of itself that Spain wishes to project: a country whose reputation also transmits a series of beliefs and values (Belief System).  These images, together with a system of ideas and beliefs that provide a framework for the interpretation of who Spain is, must safeguard the country’s image as a sound and reliable actor while transmitting a set of ideas and values based on commitment and solidarity in this area, thus contributing to an overall positive image of the country.
Keywords: Images; Perceptions; Reputation; Peace Operations; Spain; International Relations